The Wiz [videorecording (DVD)] - Schumacher, Joel, 1939-2020; Ross, Diana, 1944-; Jackson, Michael, 1958-2009; Russell, Nipsey, 1924-2005; Pryor, Richard, 1940-2005; Horne, Lena; Ross, Ted (Theodore); Morris, Oswald, 1915-2014; Jones, Quincy, 1933-; Small, Charles, 1927-2017; Brown, William F. (William Ferdinand), 1928-2019; Baum, L. Frank (Lyman Frank), 1856-1919 (Wizard of Oz, 1999)
A discontented kindergarten teacher living in Harlem is lost in a blizzard and comes upon the wonderland of Oz. There she meets new friends, tries to find her way home, and finds that her life is not so bad after all.